Sarah, plain and tall - MacLachlan, Patricia (New York HarperTrophy, 1985)
When their father invites a mail-order bride to come to live with them in their prairie home, Caleb and Anna are captivated by her and hope that she will stay.
Keywords: Children's stories, American -- Fiction; Stepmothers -- Fiction; Frontier and pioneer life -- Fiction